2015
DOI: 10.1038/jes.2015.42
|View full text |Cite
|
Sign up to set email alerts
|

Role of clothing in both accelerating and impeding dermal absorption of airborne SVOCs

Abstract: To assess the influence of clothing on dermal uptake of semi-volatile organic compounds (SVOCs), we measured uptake of selected airborne phthalates for an individual wearing clean clothes or air-exposed clothes and compared these results with dermal uptake for bare-skinned individuals under otherwise identical experimental conditions. Using a breathing hood to isolate dermal from inhalation uptake, we measured urinary metabolites of diethylphthalate (DEP) and di-n-butylphthalate (DnBP) from an individual expos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
137
0
7

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 115 publications
(149 citation statements)
references
References 35 publications
5
137
0
7
Order By: Relevance
“…Morrison et al . observed substantial uptake of diethyl phthalate (DEP) and di‐n‐butyl phthalate (DnBP) for a subject wearing clothing that had been allowed to absorb the phthalates for 9 days from chamber air enriched in DEP and DnBP.…”
Section: Introductionmentioning
confidence: 99%
“…Morrison et al . observed substantial uptake of diethyl phthalate (DEP) and di‐n‐butyl phthalate (DnBP) for a subject wearing clothing that had been allowed to absorb the phthalates for 9 days from chamber air enriched in DEP and DnBP.…”
Section: Introductionmentioning
confidence: 99%
“…levels of gas-phase nicotine for a longer time, absorbing more nicotine. With sufficient exposure time, at the same gas-phase concentration as in the 3-h bare-skin and clean-clothes exposure, dermal uptake from clothing could exceed that for bare-skinned participants as was observed for phthalates in Morrison et al (2016).…”
Section: Accepted Articlementioning
confidence: 82%
“…On the other hand, wearing clean clothing after exposure is anticipated to significantly reduce absorption due to transfer of nicotine from skin lipids to clothing (Weschler et al, 2015;Morrison et al, 2016). Given such transfer to clothing, the absorbed mass measured in this study is likely within a factor of five of the maximum anticipated absorption (neglecting ionization).…”
Section: Accepted Articlementioning
confidence: 84%
“…Fabrics are recognized as a possible exposure route, but there have been few studies concerning transport of chemicals to textile materials from air. 30 Morrison et al 31 recently evaluated the influences of freshly cleaned and pre air-exposed clothes (clean cotton clothes exposed to phthalates for at least 1 week prior to use) on dermal exposure to phthalates, DEP and DnBP, with the clothed participants being exposed to phthalates vapor in a chamber. After 6 h exposure, urine samples of the participants with pre air-exposed clothes contained greater concentrations of DEP and DnBP metabolites than those of the participants with fresh clothes.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The results indicated that freshly cleaned clothes were protective, whereas pre air-exposed clothes enhanced dermal uptake of DEP and DnBP by the factors of 3.3 and 6.5, respectively, compared to the average results for bare-skinned participants. 31 Accordingly, clothes with sorbed pollutants may substantially enhance dermal uptake of SVOCs compared to bare skin, even if the exposure is nonoccupational. In addition, gaseous methamphetamine, a substituted amphetamine and central nervous system stimulant, was reported to accumulate on cotton and polyester clothes, toy fabrics, upholstery, and skin oil.…”
Section: ■ Introductionmentioning
confidence: 99%